Empowerment of Women Inmates Category IIB Correctional Institution Jambi Through CSR Program of PT Pertamina EP Jambi Field - Tasmat, Djulianto; Afrianto; Arifin, M. Zainul; Septiawati, Oky; Safrida (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
The high rate of criminality among inmates, especially in regard to drug-related issues, is inseparable from the problems of inequality that occur in social life. Economic factors are the trigger for these problems. In addition, the negative stigma experienced by ex-prisoners inevitably leads them to fall back into their bad deeds, so if left uncontrolled, the unbreakable cycle will continue. Solutions to these problems must be found in order to reduce or even eliminate them. This research was conducted to highlight what factors have led to the high recidivist rate of former residents of the Jambi category IIB Prison. Furthermore, this paper will also include what steps can be taken to reduce social problems that occur after the sentencing of prisoners of Category IIB Jambi Women's Prison. This research uses a qualitative approach. The qualitative approach in this study is to describe the results of research in the form of written or spoken words obtained from observation, interviews, and documentaries. This research discusses: (1) The main problems that cause the high recidivism rate in the Jambi Category IIB Women's Prison. (2) How PT Pertamina EP Jambi Field initiated an empowerment program to overcome these social problems. (3) How the program provides solutions to the problems that occurred. The implementation of the program must involve stakeholders, including the government, in this matter the Jambi Category IIB Women's Prison, NGOs with the private sector, and the community.